Dinâmica de reorientação de cristais líquidos nemáticos dopados com nanopartículas de ouro - Santos, Rafael Vieira dos (2016)
In recent years, the interest in improving the properties of liquid-crystalline systems by using metallic nanoparticles has grown. This is because these materials have particular optical and electrical characteristics, associated with the plasmon resonance phenomenon. Recently, several studies have shown that the addition of gold nanoparticles affects the electrical response of liquid crystals depending on the nanoparticles geometry and the liquid-crystalline alignment. In this study, we investigated the effects of the addition of gold nanoparticles with different geometries on the relaxation time of the 4-octyl-4-cyanobiphenyl (8CB) liquid crystal, under the helical confinement conditions. We used an experimental setup that explores the Brewster angle to investigate how the application of a external electrical field and temperature of the system affect the reorientation dynamics of the director vector nearby the transition of nematic-smectic-A phase. The results obtained were analyzed within the elastic theory of Franck-Oseen e allowed us to evaluate the effects of nanoparticles on the viscoelastic parameters of the system. Our results show that the addition of nanoparticles significantly affects the electro-optical response of the investigated liquid crystals, especially in conditions of high temperature and low amplitude of the applied electrical field. In addition, we have observed that the geometry of the nanoparticles plays a key role in the modification of the electro-optical properties of the system.